The Dynamic Effect of Social and Political Instability on Output : The Role of Reforms - Bernal-Verdugo, Lorenzo E. (IMF Working Papers; Working Paper ;, 2013)
The aim of this paper is to analyze the dynamic effect of social and political instability on output. Using a panel of up to 183 countries from 1980 to 2010, the results of the paper suggest that social conflicts have a significant and negative impact on output in the short-term with the magnitude of the effect being a function of the intensity of political instability. The results also show that the recovery of output over the medium-term depends on the ability of the country to implement, in the aftermath of a social instability episode, reforms aimed at improving the level of governance. The results are robust to different checks and estimation strategies.